2006
DOI: 10.1089/mdr.2006.12.33
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Implications ofStaphylococcus aureuswith a Vancomycin MIC of 4µg/ml in Korea

Abstract: In addition to vancomycin-intermediate Staphylococcus aureus (VISA), S. aureus with a vancomycin MIC of 4 microg/ml has been reported to be the cause of therapeutic failure. This study was designed to determine the prevalence of methicillin-resistant S. aureus (MRSA) with a vancomycin MIC of 4 microg/ml and to clarify the clinical characteristics of infections caused by these isolates. During the 8-week period from April to May, 2001, 27 hospitals participated in a nationwide surveillance program for VISA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…However, the multicenter design and the enrollment of a relatively large number of ISA cases in a prospective manner are important factors when considering differences between our results and those of studies performed at the level of individual centers. The prevalence of h-VISA among ISA infections was low in our study, which is in agreement with previous nationwide surveillance studies of clinical isolates (2,3). However, the prevalence of h-VISA in a recent study by Park el al.…”
Section: H Eteroresistant Vancomycin-intermediate Staphylococcus Auresupporting
confidence: 93%
See 1 more Smart Citation
“…However, the multicenter design and the enrollment of a relatively large number of ISA cases in a prospective manner are important factors when considering differences between our results and those of studies performed at the level of individual centers. The prevalence of h-VISA among ISA infections was low in our study, which is in agreement with previous nationwide surveillance studies of clinical isolates (2,3). However, the prevalence of h-VISA in a recent study by Park el al.…”
Section: H Eteroresistant Vancomycin-intermediate Staphylococcus Auresupporting
confidence: 93%
“…showed that h-VISA was very rare in Korea (2,3). However, the prevalence of h-VISA among cases of methicillin-resistant S. aureus (MRSA) bacteremia reached 37.7% in a recent study performed in a Korean hospital (4).…”
Section: H Eteroresistant Vancomycin-intermediate Staphylococcus Aurementioning
confidence: 99%
“…This is significant because to date only MRSA isolates have been reported with reduced susceptibility to vancomycin [24][25][26][27] . S. aureus isolates with reduced vancomycin susceptibility is clinically significant because these isolates have been shown to express heterogeneous resistance to vancomycin that resulted in treatment failure [26,27] . In heterogeneous resistance, a subpopulation of cells expresses resistance, whereas the majority of the cells appear susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic susceptibility was determined by the disc diffusion method, as recommended by the CLSI (2005). PFGE was performed as described previously (Kim et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotic susceptibility was determined by the disc diffusion method, as recommended by the CLSI (2005). PFGE was performed as described previously (Kim et al, 2006).Preparation of endothelial cells. Human umbilical vein endothelial cells (HUVECs) were used in these experiments.…”
mentioning
confidence: 99%